HPV Vaccination: Attitude and Knowledge among German Gynecologists - Kolben, T. M.; Dannecker, C.; Baltateanu, K.; Goess, C.; Starrach, T.; Semmlinger, A.; Ditsch, N.; Gallwas, J.; Mahner, S.; Friese, K.; Kolben, T. (Geburtshilfe und Frauenheilkunde, 2016)
Purpose: In order to achieve a higher vaccination rate, education on HPV as well as options for prophylaxis performed by doctors is of great importance. One opportunity to increase the protection against HPV would be vaccinating boys. This study evaluated attitude and knowledge among German gynecologists regarding HPV vaccination, especially in boys. Material and Methods: A questionnaire with 42 questions about demographics, attitude and knowledge about HPV and HPV vaccination was sent to members of the German Society for Gynecology and Obstetrics (DGGG). Results: 998 out of 6567 addressed gynecologists participated. Knowledge about HPV, associated diseases and possible HPV vaccines was high among participants. The attitude towards vaccination in boys as well as girls was positive. Only 8.2 % refused to vaccinate their sons whereas 2.2 % refused to do this for their daughters. However, only few gynecologists vaccinated their daughters and sons against HPV. Main reason for girls was an age outside of vaccination guidelines; for boys it was the lack of cost coverage. Conclusion: The willingness of gynecologists to perform HPV vaccination in boys is as high as for girls. However, sons of gynecologists are only rarely vaccinated against HPV. Main reason is the lack of cost coverage. Vaccinating boys could decrease the disease burden in males, as well as protect women by interrupting ways of transmission. Since the main argument against vaccination of boys is only of financial nature, the necessity of a vaccination recommendation for boys needs to be re-evaluated taking into account the cost-reduced 2-dose vaccination scheme.
Keywords: HPV; HPV vaccination; Gardasil; Cervarix; Gardasil-9